A PROFILE OF MOTHERS-TO-BE AND THOSE ACCOMPANYING THEM IN ACCOMPANIED-BIRTH WORKSHOPS - Márcia de Almeida Santana; Silvana Regina Rossi Kissula Souza; Dulce Maria Rosa Gualda; Marilene Loewen Wall (Universidade Federal do Paraná, 2012)
The exploratory and descriptive research was intended to shed light on the profile of participants in the workshops run as part of the preparation for accompanied birth extension project at a maternity school in the city of Curitiba in the state of Paraná. Data collection took place between March and May 2010 involving 53 pregnant women and the people accompanying them to the birth, via a semi-structured questionnaire on various factors including socio-demographic, obstetric and others related to accompanied birth. It was observed that the majority of the women were pregnant for the first time, educated to senior high school level and aged between 19 and 25; the pregnant women cited the necessity of preparation and safety for the birth and their desire for their partner to be present at the birth; they were unaware of the 'Law for Accompanied Birth', which gives women the right to have a companion present during birth. It is noted that this legal right is little-mentioned by the health services, it being necessary for health teams and particularly nurses to adopt strategies in the pre-natal phase for clarifying this right to women and their family members.